Implementasi Metode Moora Pada Sistem Pendukung Keputusan Untuk Pemilihan Hotel Terbaik Di Kota Medan - Marpaung, Preddy; Siahaan, R. Fanry; Febrian, Ibnu; Putri, Widia (Jurnal Mahajana Informasi, 2022)
A hotel is a temporary lodging place intended for the general public, both individually and in groups, who come from different areas as well as for the people in the area. Hotels are often used by the community as a place to rest or stay because they are considered a comfortable place to rest or other things that support the convenience of the community. The development of hotels in various cities can be said to be very rapid, judging by the large number of hotels, both star and jasmine class, which are scattered in various cities in Indonesia, one of which is Medan City. According to the central statistics agency for North Sumatra in 2017 the city of Medan has 11,366 hotels. With the large number of hotels in the city of Medan scattered in several locations with various hotel classes, hotel rates and hotel facilities make it difficult for people to determine which hotel is appropriate according to existing criteria. If you choose the wrong hotel where to stay where there are no guarantees such as comfort, facilities and others as desired, it will not have an impact on people who want to stay overnight. Therefore it is necessary to implement a method to support a decision support system for choosing the best hotel in the city of Medan according to the desired criteria. Researchers implemented the Multi-Objective Optimization by Ratio Analysis method or commonly abbreviated as the MOORA method in a decision support system to choose the best hotel in the city of Medan. The reason researchers use this method is because several previous researchers used a lot of decision support systems using the MOORA method in solving problems in decision makers. With this research, the public will gain new knowledge to choose hospitality in the city of Medan. Where the outcome promised by the researchers in this study is the sinta 5 accredited journal.